Preliminary results of the research of the Woozle Hill outcrop (West Antarctica) - I. R. Savchyn; Ye. O. Shylo; I. M. Bubniak; A. M. Bubniak (Ukrainian Antarctic Journal, 2019)
The purpose of the work. Demonstrate the ability to apply the latest techniques, namely digital photogrammetry, to construct virtual geological outcrops in difficult natural environments, and identify the advantages and disadvantages of this approach. Method. A research algorithm based on planning, field measurements, processing and analysis of results is proposed and used. The planning included reconnoitring the site and creating a working project. At the stage of the field measurements were performed fixing and determining the coordinates of the control and basis points, as well as digital photogrammetric shooting. Photogrammetric photography was performed using a Canon 5D Mark III digital camera. When processing the results, the following was performed: external orientation of the images; selection of characteristic connecting points; building a digital terrain model. Agisoft Metashape software was used to process the results. The analysis of the results involves: an assessment of the accuracy of the constructed digital terrain model; extraction of planes; construction of stereograms of cracks. The result analysis used Cloud Compare software. Results. Using normal and rejected cases, on February 14, 2019, the photogrammetric survey of the Woozle Hill (Galindez Island) outcrop was performed. As a result of the shooting we obtained 177 pictures, which are the base of the 3D model. Conclusions. On the basis of this model information on the orientation of joints was obtained. A stereogram and a rosette were constructed. The predominant directions of joints and their angles of dipping are revealed. The advantages of the proposed approach for the study of outcrops in hard-to-reach areas are demonstrated, and their high accuracy is indicated. The disadvantages are the dependence of the workflow on the weather. Among other possible applications, the model can be used to visualize the Woozle Hill outcrop, as well as to create virtual excursions. tual excursions.